Fatigue studies on carbon steel piping welded materials and its connections: article - Mat Isa, Ridzuan; Abdul Razak, Khalil (2018)
In this study, the fatigue characteristics in pipe is investigated to increase the knowledge of the fatigue crack growth in pipe. The material used in this study is carbon steel. This study does a simulation of the fatigue crack growth of a created model. This simulation uses a software called ABAQUS, this software uses extended finite element analysis as a platform to simulate the changes happen to the model when in different condition.